2021
DOI: 10.3389/fonc.2021.675877
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Combined Model for Preoperative Prediction of Lymph Node Metastasis in Peripheral Lung Adenocarcinoma

Abstract: BackgroundBased on the “seed and soil” theory proposed by previous studies, we aimed to develop and validate a combined model of machine learning for predicting lymph node metastasis (LNM) in patients with peripheral lung adenocarcinoma (PLADC).MethodsRadiomics models were developed in a primary cohort of 390 patients (training cohort) with pathologically confirmed PLADC from January 2016 to August 2018. The patients were divided into the LNM (−) and LNM (+) groups. Thereafter, the patients were subdivided acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Hattori et al 16 confirmed the significance of the presence of an air bronchogram in the lung adenocarcinoma as a predictor of LN-negative metastasis. However, Li et al 13 reported that tumors with an air bronchogram were more common in the LN-positive metastasis group than in the LN-negative metastasis group. Further validation with larger sample size is needed to confirm these results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hattori et al 16 confirmed the significance of the presence of an air bronchogram in the lung adenocarcinoma as a predictor of LN-negative metastasis. However, Li et al 13 reported that tumors with an air bronchogram were more common in the LN-positive metastasis group than in the LN-negative metastasis group. Further validation with larger sample size is needed to confirm these results.…”
Section: Discussionmentioning
confidence: 98%
“…Malignant lesions tend to cause pleural thickening and indentations close to the pleura. 13,14 Malignant tumors are prone to LN metastasis. The risk of LN metastasis is greater in lung adenocarcinomas, which are diagnosed as solid lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, radiomics has received increasing attention, and it is a technique for high-throughput extraction of quantitative features from medical images (10,11). Indeed, many studies have exhibited that quantitative radiomic image features of the primary tumor could be used as non-invasive biomarkers to predict LNM and were good predictive performance (12)(13)(14). For OLM of LUAD, Zhong et al (15) reported that the radiomics signature of the primary tumor based on CT scans had a significant predictive value.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics, as an emerging discipline, can non-invasively transform medical images into multidimensional, potential information through quantizing features that are imperceptible to the naked eyes, and explore features’ associations with pathophysiological changes [ 16 , 17 , 18 ]. Recently, radiomics analysis in the brain, lung, pancreas and prostate is widely applied with the progress of state-of-the-art informatic technology, aiming to achieving computer-aided-diagnosis and providing clinical support in the decision-making process [ 19 , 20 , 21 , 22 ]. Past studies denoted the success of radiomics depend on interpretability, repeatability and reproductibility of constructed models.…”
Section: Introductionmentioning
confidence: 99%